IN VITRO ANALYSIS OF MIGRATION ACTIVITY OF ENCEPHALYTOGENIC T CEL - M. A. Nosov; E. A. Korneva (Медицинская иммунология)
Experimental autoimmune encephalomyelitis in an adoptive transfer model is caused by injecting animal with activated T cells specific for a CNS antigen, e.g., basic myelin protein. Development of autimmune inflammation in such a model is connected with changed functional stateof encephalytogenic (EG) T cells in the coure of disease progression, as reflected by changes in their activation, proliferation and motility levels. Present work describes an original technique allowing for in vitro analysis of encephalytogenic T cell motility, and studying effects of certain compomemts of extracellular matrix upon migration and functional activities of EG T cells.